2003
DOI: 10.1074/jbc.m210194200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Receptor Tyrosine Kinase Signaling by Protein Tyrosine Phosphatase-1B

Abstract: Receptor tyrosine kinases (RTKs) are key regulators of cellular homeostasis. Based on in vitro and ex vivo studies, protein tyrosine phosphatase-1B (PTP1B) was implicated in the regulation of several RTKs, yet mice lacking PTP1B show defects mainly in insulin and leptin receptor signaling. To address this apparent paradox, we studied RTK signaling in primary and immortalized fibroblasts from PTP1B ؊/؊ mice. After growth factor treatment, cells lacking PTP1B exhibit increased and sustained phosphorylation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
205
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(213 citation statements)
references
References 60 publications
7
205
1
Order By: Relevance
“…30 In this step, PTP1B deficiency increased tyrosine autophosphorylation of EGFR and HGFR in hepatocytes and regenerating liver. This result agrees with the increased phosphorylation of EGFR reported in PTP1B Ϫ/Ϫ fibroblasts, 3 whereas sustained HGFR tyrosine phosphorylation in response to an apoptotic trigger has been described in the livers of PTP1B Ϫ/Ϫ mice. 42 Moreover, our results revealed that PTP1B modulates the early signaling pathways activated downstream of receptors of the tyrosine kinase superfamily in hepatocytes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…30 In this step, PTP1B deficiency increased tyrosine autophosphorylation of EGFR and HGFR in hepatocytes and regenerating liver. This result agrees with the increased phosphorylation of EGFR reported in PTP1B Ϫ/Ϫ fibroblasts, 3 whereas sustained HGFR tyrosine phosphorylation in response to an apoptotic trigger has been described in the livers of PTP1B Ϫ/Ϫ mice. 42 Moreover, our results revealed that PTP1B modulates the early signaling pathways activated downstream of receptors of the tyrosine kinase superfamily in hepatocytes.…”
Section: Discussionsupporting
confidence: 91%
“…Both HGFR and EGFR are members of the PTP1B substrate family. 3 Thus, we hypothesized that tyrosine phosphorylation of these receptors would be increased immediately after PH in the livers of PTP1B Ϫ/Ϫ mice compared with controls. To test this hypothesis, we performed Western blot analysis with anti-phospho-specific antibodies that recognize the activated forms of EGFR or HGFR.…”
Section: Increased Egfr and Hgfr Tyrosine Phosphorylation In Livers Omentioning
confidence: 99%
See 1 more Smart Citation
“…Tyrosine dephosphorylation of active ErbB receptors can occur through phosphatases, including density-enhanced phosphatase-1 (DEP1) [80] and protein tyrosine phosphatase PTP1B [81]. Dephosphorylation has the capacity to down-regulate activated receptors through abolishment of binding sites for signaling intermediates and adaptor proteins.…”
Section: Signal Attenuationmentioning
confidence: 99%
“…Since HG increases polyol pathway flux and activates PKCβ II [8,28], the influence of this pathway and PKCβ II on receptor level were investigated. A major finding was that at the higher PDGF-BB concentration (1,800 pmol/l) in HG, PKC inhibitors (calphostin C: general PKC inhibitor; or LY379196: PKCβ II -specific inhibitor at 200 nmol/l [8]) or AR inhibitors (alrestatin and sorbinil) increased receptor levels, eliminating the difference between NG and HG.…”
Section: Pdgf-bb and Glucose Effects On Pdgf-βr Protein Levelmentioning
confidence: 99%